Directions for the Reconstruction of the Tax System in Poland – a Growth‑Enhancing Proposal - Karnowski, Jakub; Rzońca, Andrzej (Acta Universitatis Lodziensis. Folia Oeconomica, 2021)
The paper aims to present directions for the growth‑enhancing reconstruction of the tax system in Poland. It presents a diagnosis of the main strengths and weaknesses of that system. Based on this diagnosis and a review of the literature, the authors propose a package of recommendations whose introduction would be conducive to economic growth. The recommendations include: shifting the burden of taxation from income, in particular low labour income, to consumption; exempting low earners from a part of social security contributions; the introduction of the possibility for local governments to increase the PIT-free allowance above the centrally set base amount; the unification of the basis for the PIT, National Health Fund and Social Insurance Institution contributions; the elimination of differences in contributions for different types of contracts on the basis of which work is performed; the extension of one‑off amortisation to all machine investments; and the elimination of sectoral taxes.